2009
DOI: 10.1136/jnis.2009.000323
|View full text |Cite
|
Sign up to set email alerts
|

Results of cutting balloon angioplasty for carotid artery in-stent restenosis in six patients: description of the technique, long-term outcomes, and review of the literature

Abstract: Cutting balloon angioplasty is an effective initial treatment for severe carotid in-stent restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Also, the 1-month patency without restenosis after cutting balloon angioplasty was 5/6 (83%), and the patency without restenosis was 4/5 (80%) after 20 months follow-up adopting the cutting balloon angioplasty. 28 For the patients using CEA for carotid ISR, Borst et al reported that all four surgically treated patients remained asymptomatic and without recurrent restenosis over a mean follow-up time of 13 months. 34 Marcucci et al and Reichmann et al all described that patients with a normal patency of the surgical correction were without recurrent restenosis during the follow-up period, 35,36 while Yu et al reported that one patient occurred recurrent symptomatic restenosis (90%) 1 year later and all other patients remained asymptomatic and without recurrent restenosis.…”
Section: Angioplasty Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the 1-month patency without restenosis after cutting balloon angioplasty was 5/6 (83%), and the patency without restenosis was 4/5 (80%) after 20 months follow-up adopting the cutting balloon angioplasty. 28 For the patients using CEA for carotid ISR, Borst et al reported that all four surgically treated patients remained asymptomatic and without recurrent restenosis over a mean follow-up time of 13 months. 34 Marcucci et al and Reichmann et al all described that patients with a normal patency of the surgical correction were without recurrent restenosis during the follow-up period, 35,36 while Yu et al reported that one patient occurred recurrent symptomatic restenosis (90%) 1 year later and all other patients remained asymptomatic and without recurrent restenosis.…”
Section: Angioplasty Efficacymentioning
confidence: 99%
“…26 For the treatment of regular balloon angioplasty, the stenosis rates decreased to 16% in Zhou et al's study after intervention. 14 For the treatment of common or cutting balloon angioplasty, the study of Donas et al showed that the primary and assisted primary patency rates were 68.8%, 27 while the angiography stenosis rates also decreased to 20% after treatment (Heck's study 28 ). At last, the therapeutic of CEA could also significantly solve the problem of carotid ISR.…”
Section: Angioplasty Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…81 Recurrent focal neurologic deficit months or years after CAS suggests in-stent restenosis, which may be treated using a cutting balloon with distal embolic protection. 82,83…”
Section: Complications Of Extracranial Carotid Angioplasty and Stentingmentioning
confidence: 99%
“…Flush all catheter systems continuously with heparinized saline. 13 Use a larger diameter 90-cm sheath (e.g., 8F sheath) and a 0.014 or 0.018-in. wire anchored into a branch of the ECA.…”
Section: Access Phasementioning
confidence: 99%